(untitled) - Ouchi, William G. (Reading, 1981)
This four-month New York Times bestseller not only explains incredible Japanese productivity levels, but also offers a plan to revitalize corporate America. Ouchi outlines what we can learn from Japanese business success and how we can put it to use here in the U.S.
Keywords: Industrial management